Molecular Docking of Robustaflavone Derivatives on Pi3k Protein Target and The Correlation With Its Cytotoxic Activity on Cancer Cells - Sri Handayani; Zalinar Udin (Indonesian Society for Cancer Chemoprevention, 2011)
Robustaflavone derivatives have cytotoxic effect on cancer cell. Inhibition of PI3K on cancer cell has correlation with apoptotic induction. The aim of this research is to observe interaction from robustaflavone derivatives on PI3K receptor that may give contribution to the cytotoxic effect of the compounds on cancer cell line. Geometric optimization of robustaflavone derivatives structured was done used Hyperchem 7.5 software. Arguslab 4.01 software with GAdock method applied for the docking step. The docking result showed that robustaflavone 7,4',7''- trimethyl ether (RTE) has affinity on PI3K target receptor which gave the lowest Gibbs free energy (∆G -10,855 kcal/mol).Keywords: robustaflavone, PI3K, cancer, docking